Novel frameshift variant in the PCNT gene associated with Microcephalic Osteodysplastic Primordial Dwarfism (MOPD) Type II and small kidneys - Hettiarachchi, D (Springer Science and Business Media LLC, 2022)
10.1186/s12920-022-01226-8